Correlation between microalbuminuria and glycosylated haemoglobin and cardiovascular disease in diabetic patients: a case-control study - Subramani, Jayaprakash; ., Prabhusamy (International Journal of Research in Medical Sciences, 2016)
Background: Microalbuminuria is an independent risk factor for cardiovascular mortality in both diabetic and non-diabetic individuals. Our aim was to assess the incidence of elevated glycosylated haemoglobin and cardiovascular disease in relation to microalbuminuria in diabetic patients. Methods: Diabetic patients with or without microalbuminuria were assigned into two groups. Each group consisted of 100 patients. Patients with co-morbid conditions which contribute to microalbuminuria were excluded from this study. Data on clinical features, fasting and postprandial blood glucose, HbA1C (glycosylated haemoglobin) level, urine microalbumin levels, renal parameters, cardiovascular events, diabetic retinopathy changes were collected for both groups and compared. Results: Majority of patients were in 5th and 6th decade with male to female ratio of 2.5:1 in microalbuminuria group and 1:1.1 in non-microalbuminuria group. Mean duration of diabetes was 4.3 yrs in patients with microalbuminuria; and 3.5 yrs in patients without microalbuminuria. Incidence of elevated glycosylated haemoglobin (HbA1c ≥ 6.5%) in microalbuminuria group was 69%; in patients without microalbuminuria was 43%. Incidence of coronary artery disease (CAD) was 32% in microalbuminuria group; 16% in patients without microalbuminuria. These differences were statistically significant. Diabetic retinopathy was observed in 23% of patients in microalbuminuria group; 19% in patients without microalbuminuria. Conclusions: Microalbuminuria in diabetic patients was significantly associated with poor glycaemic control. It was strongly associated with longer duration of diabetes. Incidence of cardiovascular events was higher in patients with microalbuminuria compared to patients without microalbuminuria.